Aujeszky’s Disease and Hepatitis E Viruses Transmission between Domestic Pigs and Wild Boars in Corsica: Evaluating the Importance of Wild/Domestic Interactions and the Efficacy of Management Measures - Charrier, François; Rossi, Sophie; Jori, Ferran; Maestrini, Oscar; Richomme, Céline; Casabianca, François; Ducrot, Christian; Jouve, Johan; Pavio, Nicole; Le Potier, Marie-Frédérique (Frontiers in Veterinary Science, 2018)
Wildlife species as reservoirs of infectious pathogens represent a serious constraint in the implementation of disease management strategies. In the Mediterranean island of Corsica, the dynamics of Hepatitis E virus (HEV) and Aujeszky’s Disease virus (ADV) are suspected to be influenced by interactions between wild and domestic pigs. To improve our understanding of these influences, we first compared the seroprevalences of both viruses in domestic pig populations from different locations with contrasted levels of wild-domestic interactions, ADV vaccination, biosafety and farm husbandry. Secondly, we performed an analysis at a more restricted geographical scale, in order to assess the matching of ADV or HEV prevalence between sympatric wild boar and outdoor pig farms most exposed to interactions with wildlife. Logistic models were adjusted to the observed data. A high seroprevalence of HEV (>80%) and ADV (40%) in pigs, with no significant difference according to the region, confirms that both pathogens are enzootic in Corsica. Vaccination against ADV had a strong protective effect, even when performed voluntarily by farmers. Farm biosafety had an additional effect on pigs’ exposure, suggesting that contact between wild boars and pigs were involved in disease transmission. A strong correlation in HEV seroprevalence was observed between pigs and wild boars that were in close contact and significantly lower seroprevalence was observed in pigs when they had little contact with wild boars due to spatial segregation. These results suggest a regular HEV circulation between sympatric wild boar and domestic pigs. The high HEV seroprevalence observed in domestic pigs (>80%) suggests a spillover of the virus from domestic to wild populations through environmental contamination, but this hypothesis has to be confirmed. Conversely, even though avoiding sows’ release on pasture during oestrus showed some protecting effect in the free ranging pig farms regarding ADV, ADV seroprevalence was not dependent on the swine populations (wild or domestic) or on the wild-domestic spatial overlap, suggesting two quasi-separate enzootic cycles. This information will prove useful for designing more efficient disease management strategies in Corsica and similar contexts.